A review of thermal interface material fabrication method toward enhancing heat dissipation - Bahru R.; Zamri M.F.M.A.; Shamsuddin A.H.; Shaari N.; Mohamed M.A. (John Wiley and Sons Ltd, 2023)
Electronic equipment; Fabrication; Hybrid materials; Interfaces (materials); Nanostructured materials; Thermal insulating materials; Electronic device; Fabrication method; Industrial markets; Material fabrication; Performance of devices; Surface temperatures; Thermal interface materials; Thermal Performance; Thermal conductivity